2004
DOI: 10.1002/gea.20013
|View full text |Cite
|
Sign up to set email alerts
|

Late holocene behavior of Chaco and McElmo Canyon drainages (Southwest U.S.): A comparison based on archaeologic age controls

Abstract: Two outwardly similar shallow‐canyon drainages of the Four Corners region of the Colorado Plateau (southwestern U.S.), McElmo Creek (SW Colorado) and Chaco Wash (NW New Mexico), expose late Holocene units which have been dated by numerous remains of the puebloan Anasazi culture (A.D. 500–1300). The stratigraphic sequences, though composed of similar sediment facies, show markedly different evolutions. The McElmo Canyon sequence consists of two units separated by an unconformity that apparently represents an ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 28 publications
0
7
0
Order By: Relevance
“…It is unknown whether these age reversals are caused by old wood or by the reworking of previously deposited charcoal. A fi nal complication in interpreting alluvial history comes from the complex geomorphic responses of different streams and different reaches of the same stream to the same environmental drivers Schumm, 1975, 1981;Force, 2004). We dealt with these actual and potential problems as follows.…”
Section: Interpreting the Stratigraphic Sectionsmentioning
confidence: 56%
“…It is unknown whether these age reversals are caused by old wood or by the reworking of previously deposited charcoal. A fi nal complication in interpreting alluvial history comes from the complex geomorphic responses of different streams and different reaches of the same stream to the same environmental drivers Schumm, 1975, 1981;Force, 2004). We dealt with these actual and potential problems as follows.…”
Section: Interpreting the Stratigraphic Sectionsmentioning
confidence: 56%
“…Similar timing of incision over a broad geographic area supports an allogenic (climatic) control for arroyo cutting (Karlstrom and Karlstrom, 1987;Karlstrom, 2005;Daniels, 2008). However, nonsynchroneity of cutting episodes for some basins in the Holocene indicates that factors other than climatic change may contribute to the timing of arroyo incision (Patton and Schumm, 1981;Patton and Boison, 1986;Karlstrom and Karlstrom, 1987;Elliott et al, 1999;Force, 2004). The recent arroyo cutting episode in the late nineteenth and early twentieth centuries has generally been attributed to three causes: (1) climate change (Leopold and Snyder, 1951;Balling and Wells, 1990;Hereford, 2002), (2) human factors such as overgrazing (Thornthwaite et al, 1942;Cooke and Reeves, 1976) and dam failures (Love, 1997), and (3) intrinsic geomorphic processes and thresholds (Schumm and Hadley, 1957;Pederson 2000).…”
Section: Arroyo Cyclementioning
confidence: 93%
“…Late Quaternary studies in the Southwest that support this model include work by Force (2004). By contrast, several studies do not fi nd support for time-transgressive alluvial stratigraphy in paleoarroyos (Karlstrom and Karlstrom, 1987;Hereford, 2002).…”
Section: Arroyo Modelsmentioning
confidence: 95%
“…For example, Force et al. () and Force (), working near Chaco Canyon National Monument in northern New Mexico, suggested that Chaco Wash was intermittently dammed by eolian processes to form the so‐called “Chaco Lake” during the Pueblo II occupation there. Researchers then related cultural development at Chaco Canyon, measured by building construction, to the influence of lacustrine conditions on alluvial aggradation, channel cutting, and irrigation.…”
Section: Discussionmentioning
confidence: 99%